Efektivitas Metode Pembelajaran Home Visit Mata Pelajaran PAI Pada Masa Pandemi Covid-19 - Nurhalimah Septianingsih; Bahrun Ali Murtopo; Atim Rinawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The purpose of this research is: (1) To describe the effectiveness of the home visit learning method on PAI subjects in grades 4-6 at SD N 4 Donorojo, Sempor, Kebumen and (2) To describe the inhibiting factors and solution in the implementations of the home visit method carried out by PAI teacher at SD N 4 Donorojo. This type of research uses a qualitative approach. The students studied are students in grades IV, V, and VI at SD N 4 Donorojo, Sempor District, Kebumen Regency. The data collected in the form of interviews, observations, and also documentation. The data analysis used is descriptive analysis instrument. The data analysis technique used analyzes interactive method. Based on the results of the study, it can be concluded: 1) the use of the home visit method at SD N 4 Donorojo, Sempor District, Kebumen Regency is very effective because if you use online the condition of the internet network does not exist so that it is not possible to carry out teaching and learning activities using online or online and 2) .the obstacles that exist in SD N 4 Donorojo include Students’ houses that are far apart, the internet network that does not exist and also inadequate roads. However, apart from that, there is a solution made by PAI teachers, namely bringing 2 groups closer together with houses that are close together.